Strategic Verbal Humour in Political Leadership: A Case Study of Tun Dr. Mahathir bin Mohamed - Azmi Abdul Latiff, (Development in Language Studies, 2024)
This research is a pioneering exploration into the strategic use of verbal humour by Tun Dr. Mahathir Mohamed, a prominent figure in Malaysian politics renowned for his tenure as the twice-elected Prime Minister. Through qualitative content analysis, this study examines excerpts from Tun Dr Mahathir Mohamed's first press conference after being sworn in as Malaysia's seventh Prime Minister to classify the types of verbal humour he employs. The analysis reveals a multifaceted use of humour, encompassing self-deprecating humour, sarcasm, hyperbole, and irony, each serving distinct communicative and rhetorical functions. Importantly, these forms of humour are not used haphazardly but strategically. Self-deprecating humour, for instance, emerges as a tool for humanising the leader, making him more relatable and approachable despite past criticisms of his authoritative leadership style. Sarcasm and hyperbolic humour are identified as mechanisms for critiquing media representation and emphasising political support, effectively challenging prevailing narratives with wit and satire. The irony, interwoven with Tun Dr Mahathir Mohamed's discourse, subtly underscores the complexities of political communication, media interactions, and public engagement in the Malaysian context. The findings emphasise the complexity of humour as a strategic communication tool in leadership, illustrating its potential to enhance relatability, negotiate public image, and engage in political critique. This paper makes a significant contribution to the existing literature on political communication and leadership by highlighting the nuanced role of humour in political discourse, demonstrating how it can be skillfully deployed to navigate the intricacies of leadership and public perception. Through the lens of Tun Dr. Mahathir Mohamed's political career, this study provides valuable insights into the dynamic interplay between humour, politics, and leadership in a diverse socio-political landscape.